KONSEP PENILAIAN KINERJA GURU DAN FAKTOR YANG MEMPENGARUHINYA - Ahmad, Laode Ismail (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Law Number 20 Year 2003 on National Education System, Law Number 14 Year 2005 regarding Teachers and Lecturers, and Government Regulation Number 19 Year 2005 on National Education Standard states teachers are professional educators. Teachers as professionals have an important role in learning. The role of teachers in learning is to make learning design, organizing teaching and learning activities, teaching or learning. Efforts have been made to improve the quality of national education, such as the development of national and local curricula, improving teacher competence through training, procurement of books and instructional tools, teacher certification, procurement and improvement of educational facilities and infrastructure, and improving school management. But apparently all these efforts have not shown maximum results. Proven when people are still talking about less qualified graduates, even in terms of morals learners tanpak increasingly degenerate, honesty is very lacking, no manners, less discipline, less responsibility, shyness is very lacking, misconduct everywhere, and so on. In order to achieve the targeted goals in improving the quality of education, this is where the importance of teachers improve the quality of their performance in learning as a figure that plays an important role in advancing the world of education. To have a good performance teachers are required to have adequate academic ability, and can apply the knowledge they have to learners to advance the quality of learning learners.